The Effect of Using Digital Marketing Platforms, Optimizing Potential Assets on the Inclusive and Sustainable Economy Improvement - Gede Adi Yuniarta; I Gusti Ayu Purnamawati; Kadek Rai Suwena (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2023)
This study aims to analyze the role of the green economy and digitalization for sustainable rural economic development. This research is quantitative descriptive research. The research was conducted in Manistutu Village, Jembrana Regency, Bali Province. Research data using primary sources were collected using a questionnaire with a Likert scale. Respondents in this study were the community and village officials who carried out activities using technical assistance in government activities, tourism, agriculture, and plantations. The research sample amounted to 70 people using purposive sampling. Data were analyzed using Structural Equation Modeling. The results of the research were conducted to explain the importance of maintaining sustainable economic growth in the tourism, agriculture, and plantation sectors in the Jembrana Regency by using technology. Digital marketing platforms and optimizing the potential of village assets have a significant influence on growth in the inclusive and sustainable economic and financial sectors.